Sodni izvedenec psihološke stroke - Pavšič Mrevlje, Tinkara (Psihološka obzorja (Ljubljana), 2011)
The paper is a review of different issues that a forensic psychologists encounter at work. Forensic assessment might be needed in civil law cases, administrative procedures and in criminal law cases. The paper focuses on referrals in criminal law cases regarding matters such as assessing competence to stand trial, criminal responsibility and violence risk assessment. Finally, the role of expert testimony on eyewitness memory, which is not used in practice in Slovenia yet, is presented.
Keywords: expert testimony; izvedenstvo psihološke stroke; forensic psychology; izvedenci; criminal responsibility; sodna psihologija; prištevnost; eyewitness testimony; pričanje